Perbandingan Pengolahan Data Foto Udara Menggunakan Perangkat Lunak Agisoft Metashape Professional dan APS Menci - Ardiansyah Ardiansyah; Shabri Indra Suryalfihra; Dawamul Arifin; F. V. Astrolabe Sian Prasetya (Journal of Geomatics Engineering, Technology, and Science, 2023)
Photogrammetry is a method of mapping objects on the earth's surface using aerial photographs as a medium. Orthophoto is a product of photogrammetry. Utilization and processing of aerial photo data are increasingly widespread with the support of various adequate software. This study aims to process aerial photo data and determine differences in the quality of orthophotos produced from Agisoft Metashape and APS Menci software. In this study, 714 aerial photo data were taken using the DJI Phantom 3 pro drone, and 9 Ground Control Points were obtained from static measurements using the Comnav T300 Geodetic GPS, processed using the Agisoft Metashape and APS Menci software, starting from Georeferencing, DEM Making, DTM, Editing Semalines, and Orthophoto. The results obtained from this study visually produce orthophotos that have different lighting. APS Menci is brighter than Agisoft Metashape. In addition, there is also a difference in the area of 9.1 Ha from orthophoto where Agisoft Metashape produced 64.61 Ha while APS Menci was 55.51 Ha. The GSD (Ground Sampling Distance) value of Agisoft Metashape is 4.12 cm and APS Menci is 4.2 cm. From the results of the orthophoto semantic quality test obtained from the interpreter it gives a Level 7 score on the NIIRS (National Imagery Interpretability Rating Scale) based on the IRARS (Imagery Resolution Assessment and Reporting Standards) table, where the resulting orthophoto can detect steps on stairs. It is recommended to use the Agisoft Metashape software for better results and speed of use.